Papulonecrotic tuberculid-clinicopathologic and molecular features of 12 Indian patients - Rajalakshmi Tirumalae; Inchira K. Yeliur; Meryl Antony; Geojith George; John Kenneth (Mattioli1885, 2014)
Background: Papulonecrotic tuberculid (PNT) is said to be a hypersensitivity reaction to M. tuberculosis. Some reports indicate that organisms are demonstrable by polymerase chain reaction (PCR). Methods: We describe 12 patients with PNT over 6 years. We reviewed the histopathologic features, clinical data and follow-up. PCR for M. tuberculosis DNA was done in all cases. Results: There were 7 men and 5 women. The ages ranged from 3-58 years. Upper limbs were commonly involved (8 cases). All patients had multiple papulonodular lesions, 5 showed ulceration and scarring. Mantoux test was strongly positive in all. Seven patients had systemic tuberculosis. On microscopy, necrosis was seen in 11 cases, varying from minimal to extensive. Epithelioid granulomas were common, except for 1 case with palisading and interstitial patterns. The infiltrate showed mostly lymphocytes, while 3 cases showed eosinophils. Vasculitis was seen in 8 cases. Two cases had dermal mucin, one also with interface dermatitis. This patient had concurrent LE. Mycobacterial DNA was detectable by PCR in 3 cases. Seven patients showed improvement/resolution of lesions on treatment. Conclusions: PNT is a rare disease. A positive PCR reiterates the question whether these are "tuberculids". PNT may be better classified as true cutaneous tuberculosis and patients screened for systemic disease.